GENETIC DIVERSITY, POPULATION STRUCTURE AND EVALUATION OF BREAD WHEAT GENOTYPES UNDER HIGH TEMPERATURE STRESS - R. Farheen; M. Q. Ahmad1; M. A. Saleem; A. Qayyum; E. Noor; W. Malik; A. Saleem; S. H. Khan; S. Mahmood (Journal of Animal and Plant Sciences, 2020)
High temperature stress at reproductive stage is a prominent factor in various crop plants for yield reduction particularly wheat. In current study the performance of 50 wheat genotypes was analyzed under high temperature stress. To ascertain genetic diversity and population structure, 25 SSR markers were employed. The study was conducted for two consecutive years during 2016-17 and 2017-18 under normal and high temperature stress using randomized complete block design replicated thrice. Significant variation was found among genotypes, treatment and year factors for all the studied traits. Harvest index showed highest value of broad sense heritabilty 95.58. Genotype by trait biplot on the basis of relative performance dataset showed highest variation for yield traits (grains/spike and yield) followed by plant height, peduncle length and days to physiological maturity. The genotypes Yecora-70 and Shafaq-06 appeared tolerant because these genotypes showed less reduction in yield under heat stress. Population structure analysis grouped the genotypes into three sub-populations (A, B and C) which consisted of 15, 18 and 17 genotypes in each subpopulation, respectively. Genetic diversity values were ranged from 0.12 to 0.56 and polymorphism information contents (PIC) value from 0.11 to 0.45. Overall, the germplasm under investigation revealed low level of genetic polymorphism. Therefore, to combat challenges being posed by climate change wheat germplasm should be enriched by introducing novel genetic resources.
Keywords: Polymorphism; biplot; heterozygosity; allele; heat stress